Exploring the potential of creative museum-led activities to support stroke In-patient rehabilitation and wellbeing: A pilot mixed-methods study. Issue 2 (4th May 2023) - Morse, Nuala; Thomson, L.J.; Elsden, E.; Rogers, H.; Chatterjee, H.J.
ABSTRACT: Background: This paper proposes a framework for studying the potential of museum-led interventions for supporting stroke rehabilitation goals. Methods: The intervention was based on Kirvevold et al.'s model for interventions for post-stroke wellbeing. Mixed-methods data wqas collected to review benefits in a pilot study, including retrospective video observations for six sessions with four patients; interviews with patients, carers and facilitators; pre-post patient assessments; and facilitator diaries. Results: Systematic analysis of videos showed high levels of concentration and engagement with museum objects, low levels of social interaction, and positive or neutral mood throughout. Thematic qualitative analysis suggested patients felt engaged in meaningful activities, which lifted negative mood, provided positive distraction from the ward, and increased self-esteem, including belief in patient abilities. Conclusion: Further research is needed to fully establish the potential of museum-led interventions for stroke rehabilitation.